Pola Komunikasi Laki – Laki dan Perempuan Dalam Tradisi Karo Suku Tengger - Risky, Aulia Ighmatur; Sumardijati, Sumardijati (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The Karo traditional ceremony is often referred to as the Karo holiday or Praise Karo, which is a ritual ceremony of the Tengger Tribe which consists of various kinds of rituals. At this Karo Ceremony, the Tengger people commemorate Sang Hyang Widhi Wasa (God) who created two types of human beings (Karo), namely men and women as their ancestors. In a series of rituals performed by many men, such as the sodoran and the tip dance. Researchers investigated how the communication patterns of men and women in the Karo tradition of Jetak Village. This study used a qualitative method by trying to study deeply about the perspective of male and female communication patterns in the karo tradition of the tengger tribe, Jetak village. The results of this study indicate that the communication process that occurs between men and women in the karo tradition is a model of a divided, balanced communication pattern. Where the communication that occurs is well established and dynamic. In this pattern of communication, men and women have different areas of power. Men and women are seen as experts in different fields. During the communication process, there are different forms of conversation between men and women of the Tengger tribe. These differences can be distinguished in the form of feminine and masculine language styles. The women of the Tengger tribe will show themselves as responsive individuals and their goal is none other than to maintain friendly relations with each other, while their men will speak with clear objectives, not to beat around the bush. In addition to the form of conversation, there are different communication behaviors during the communication process between men and women, namely among them report talks conducted by men and report talk conducted by women, in the tradition of karo - men of the Tengger tribe who are more active in speaking in the public sphere and women who are more active in speaking in the private sphere (private speaking). Keywords: Communication, Karo Customs, Tengger